Activity of the inflammatory process in the respiratory tract in children with bronchial asthma - Білоус, Володимир Володимирович (Georgian Respiratory Journal, 2022)
Aim of the study: To analyze the activity of the inflammatory process in the airways in children with bronchial asthma (BA) depending on the different onset of the disease. Materials and methods: Keeping to the principles of bioethics a comprehensive retrospective examination of 319 children suffering from BA was performed. In 257 children (clinical group I) bronchial asthma developed on the background of chronic obstructive bronchitis. The second clinical group included 43 children, in whom asthma debuted after community-acquired pneumonia. The third (III) clinical group consisted of 19 children in whom asthma was first verified after inpatient treatment for asthmatic status. Results: According to the severity of bronchial asthma, it was found that the representatives of the III clinical group, compared with other patients, significantly more often had a severe course of the disease. For patients of the I clinical group in the debut is characterized by increased eosinophils and decreased neutrophil counts in sputum, for patients of group II - increased eosinophils and epitheliocytes, but a decrease in lymphocytes, and for children of clinical group III - low eosinophils sputum with a simultaneous increase in neutrophils. In particular, a statistically significant increase in the content of VEGF, a decrease in the content of cationic proteins, MMP-9, and interleukins-6, and -13 in the sputum indicates the predominance of neoangiogenesis in children of clinical group III. Instead, in the representatives of the II clinical group the remodeling processes were mainly caused by the inflammatory process with the release of intracellular eosinophilic cationic proteins. Conclusion: These data indicate the discrete nature of the type and severity of the inflammatory process of the respiratory tract in the dynamics of observation in children of clinical comparison groups, which suggests the presence of certain phenotypic differences due to the alternative onset of the disease, which in turn was determined by different triggers. Such deviations of the inflammatory process indicate that patients with asthma require a personalized approach to differentiated diagnostic monitoring and targeted anti-inflammatory treatment, taking into account the peculiarities of the onset of the disease.
Keywords: children; sputum markers; bronchial asthma